Pengaruh Kebijakan Dividen dan Konservatisme Akuntansi terhadap Kualitas Laba - Dewi Retno Mumtaz; Suwarno Suwarno (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to examine the effect of dividend policy and accounting conservatism on earnings quality in companies in the infrastructure, utilities & transportation and mining sectors listed on the Indonesia Stock Exchange (BEI) in 2019-2022. The sampling method used is a purposive sampling method based on certain criteria. From the specified criteria, a sample of 25 companies was obtained. The analytical method used is multiple linear regression analysis. The results of this research indicate that the dividend policy variable has no effect on earnings quality. Meanwhile, accounting conservatism has a significant positive effect on earnings quality.